The connection of theory and practice in music education after 2012 (Training and Practice : Journal of Educational Sciences, 2018)
The submitted paper is about the textbook knowledge topic that is closely connected to music methodology that I teach as part of my job in music teacher training. Choosing, evaluating and correcting the right textbook is an important skill to be built on for prospective music teachers. The year mentioned in the title of the paper has special importance with regards to innovation in content for music training. In 2012 the National Core Curriculum brought along changes in music teaching. The comparison between the National Core Curriculum and the various Music Framework Curricula regarding similarities and more importantly the significant differences is an inevitable task for those who currently teach and being trained to be teachers. The next step in this evaluation is the review of a chosen textbook and I will demonstrate the evaluation of a permanent textbook.